Main components and content of sports volunteer activities - Iryna Petrenkо (Kharkiv State Academy of Physical Culture, 2017)
Purpose: identification of the main structural components and content of sports volunteer activities. Material & Methods: used analysis of literature and documents, organizational analysis. Result: basic structural components of sports volunteer activity are defined. The content of sports volunteer activity is disclosed. Conclusion: sports volunteer activity includes the following structural components: subject, object, purpose, motivation, means, actions; subject is a sports volunteer, the object is a sports competition, the goal is to provide gratuitous assistance for a quality competition, the means are the special knowledge, skills, communication abilities of sports volunteers, actions should be understood as types of volunteer activities and functions that volunteers perform during the preparation and conduct of competitions. Main types of sports volunteer activity are: 1) organizational; 2) judiciary; 3) coaching; 4) legal; 5) medical. Functions that volunteers perform in the competition system are general and special. Content of the functions of sports volunteering depends on the specifics of the sports, the rank of the competition, the specifics of the competition for people with special needs.